A Study to Investigate the Barriers of Implementing Sustainable Procurement in the Chemical Industry - Goel, Sakshi (Digital Repository of Theses, 2024)
The aim of this dissertation is to explore and analyse the challenges encountered by chemical industries during the implementation of sustainable procurement practices. The chemical industry plays a pivotal role in global economic development. However, it is also one of the major contributors to environmental pollution and social issues goals face challenges in transitioning towards sustainable procurement practices. In recent years, the concept of sustainable procurement has gained significant attention to address these challenges. This research aims to provide a comprehensive analysis of sustainable procurement and its implementation in the chemical industry. It explores the importance, benefits, challenges, and best practices associated with sustainable procurement, and offers insights into successful implementation strategies specifically tailored for the chemical industry. Through an extensive review of relevant literature, case studies, and expert insights, this dissertation aims to contribute to the knowledge base on sustainable procurement in the chemical industry. This dissertation examines these challenges, identifies potential solutions, and provide recommendations for the effective implementation of sustainable procurement in the chemical industry. This study uncovers some interesting aspect of the sustainable procurement in the chemical industry from the prospective of the procurement decision makers and the executives involved in the process. This study also highlights some of the important information regarding principles, importance and need of sustainable procurement along with the challenges and finally, the study suggests some recommendations based on the findings from the respondents.